Consumer Perceptions of a Shingles Infograph Intervention and Vaccination Plans in Community Pharmacy Settings - Radhika Devraj; Miranda Wilhelm; Maithili Deshpande (INNOVATIONS in Pharmacy, 2022)
Background: Cost and lack of knowledge are key barriers to improving shingles vaccination rates in community pharmacies. A health literacy (HL) tailored infograph intervention addressing these barriers can enhance consumer interest in shingles vaccinations.